Struggle of Communist Parties in Nepal (Voice of History, 2025)
The Communist Party of Nepal appears to have been founded on Marxist ideology. Its founding members include Pushpalal Shrestha, Nar Bahadur Karmacharya, Narayan Bilas Joshi, Niranjan Govinda Baidya, and Moti Devi Shrestha. Influenced by the ongoing non-violent movement against British rule in India, the party's political objective seemed to be the liberation of the Nepali people from the threat of ultra-totalitarianism. This study focuses on the ideological issues, political strategies, and tactics of the Communist Party of Nepal, particularly in the context of other political parties that were secretly working against the Rana regime to uphold the party's independence a notion that was considered unimaginable at the time. In this way, the political activities of the Communist Party of Nepal have undergone various fluctuations. From the Shah-Rana period to the era of constitutional monarchy and eventually the democratic republic, the party’s role appears at times to have been inconsistent with its original ideological stance. The core principle of the dictatorship of the proletariat, therefore, needs to be interpreted in light of the demands and realities of changing times.